Remote Laboratory Based on the Internet of Things for E-Learning: A Development Model of Newton’s Law Experiment - Asrizal, -; Khairat, Raudhatul; Yohandri, - (Society of Visual Informatics, 2024)
Remote laboratory is a development of digital technology to support the quality of learning in this digital era. However, scientific processes often cannot be accommodated in digital spaces such as e-learning. This research highlights a remote laboratory system that can accommodate scientific process improvement in e-learning. The research objective is to develop and determine the performance of the remote laboratory system of Newton’s Law experiment based on IoT for e-learning as an experiment development model. Research methods can be classified into design and development, abbreviated as DDR. The remote laboratory system is designed and developed in six phases. This system is developed by five main components, namely, a photodiode sensor, MCU nodes, motor drivers, stepper motor, and ESP 32 CAM. The results indicate that the remote laboratory system of Newton's law experiment has demonstrated positive performance, and the accuracy and precision of measurement from the remote laboratory system are classified as high. Accordingly, the remote laboratory system of Newton's law experiment can be used as an alternative to support scientific processes in e-learning. It is expected to serve as a guide for virtual laboratory design, enlightening the audience on the potential of this system. It is used extensively for experimental teaching in modern physics education. The success in designing and developing an experimental model of Newton's law by implementing a remote laboratory based on IoT provides a good opportunity to develop various more sophisticated physics experimental systems to support the science process and e-learning.